Can Prophylactic High Flow of Humidified and Warmed Filtered Air Improve Survival from Bacterial Pneumonia and SARS-CoV-2 in Elderly Individuals? The Role of Surfactant Protein A - Ata Abbasi; David S. Phelps; Radhika Ravi; Joanna Floros (MDPI AG, 2021)
In this opinion article, we discuss a serendipitous observation we made in a study investigating survival in aged mice after bacterial infection. This observation involved a non-invasive ventilation approach that led to variable and higher survival in male and female mice with different genetic backgrounds for the innate immune molecule, surfactant protein A (SP-A). We suggest that employing the best ventilatory modality, whether that be HFNC or another method, may augment the role of other factors such as SP-A genetics and sex in a personalized approach, and may ultimately improve the outcome.